Digital Image Segmentation with Wavelet Transformation Using Matlab Version R2010b - Zainal Abidin, Muhammad (Journal of Management Economic and Financial, 2024)
One of the image processing is the segmentation process, which is a stage in the image analysis process that aims to obtain information contained in an image by dividing the image into separate areas where each area is homogeneous and refers to a clear uniformity criterion. In this paper, the application of Wavelet Transformation in the field of image segmentation by designing an application using MATLAB Version R2010B will be raised. Where wavelets are mathematical functions that cut data into different sets of frequencies, so that each of these components can be studied using different resolution scales